2016
DOI: 10.1016/j.ydbio.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of GATA motifs controlling the endoderm regulator elt-2 reveals distinct dominant and secondary cis- regulatory elements

Abstract: Cis-regulatory elements (CREs) are crucial links in developmental gene regulatory networks, but in many cases, it can be difficult to discern whether similar CREs are functionally equivalent. We found that despite similar conservation and binding capability to upstream activators, different GATA cis-regulatory motifs within the promoter of the C. elegans endoderm regulator elt-2 play distinctive roles in activating and modulating gene expression throughout development. We fused wild-type and mutant versions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Recent work inferred the binding sites for C. elegans END-1 and END-3 as RSHGATAASR and RKWGATAAGR, respectively, which are very similar though not identical (Weirauch et al 2014;Lambert et al 2019). Other work has shown that recombinant DNA-binding domains of C. elegans END-1 and END-3 can bind canonical GATA sites in the promoter of C. elegans elt-2, although END-1 has a higher affinity for such sites (Du et al 2016;Wiesenfahrt et al 2015). From this work, Endoderm GATA Domains (EGDs) immediately upstream of the DBDs show conserved amino acids between END-3s and END-1s but many more that are unique to either EGD ( Figure 10B).…”
Section: Identification Of Known and Previously Unrecognized Cis-regumentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work inferred the binding sites for C. elegans END-1 and END-3 as RSHGATAASR and RKWGATAAGR, respectively, which are very similar though not identical (Weirauch et al 2014;Lambert et al 2019). Other work has shown that recombinant DNA-binding domains of C. elegans END-1 and END-3 can bind canonical GATA sites in the promoter of C. elegans elt-2, although END-1 has a higher affinity for such sites (Du et al 2016;Wiesenfahrt et al 2015). From this work, Endoderm GATA Domains (EGDs) immediately upstream of the DBDs show conserved amino acids between END-3s and END-1s but many more that are unique to either EGD ( Figure 10B).…”
Section: Identification Of Known and Previously Unrecognized Cis-regumentioning
confidence: 99%
“…The E cell generates the entire endoderm (intestine), while its sister cell MS generates many mesodermal cell types, including the part of the pharynx, and many body muscle cells (Sulston et al 1983). Many components of the GRN underlying MS and E development are known with high precision, and in most of cases, regulatory inputs have been confirmed to be direct and cis-regulatory sites have even been identified in upstream regions (Maduro et al 2001;Broitman-Maduro et al 2005;Wiesenfahrt et al 2015;Du et al 2016). This network is therefore a highly suitable system in which to examine questions of GRN evolution and developmental system drift.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for developmentally regulated genes, 19% of their enhancers were found to drive broader reporter expression than is observed for the corresponding endogenous gene . Similar mechanisms of context dependent activity and nonadditive interactions have been observed for distinct enhancers in Arabidopsis that are acted upon by Polycomb group proteins, and for the Caenorhabditis elegans endoderm regulator elt‐2 …”
Section: Discussionmentioning
confidence: 69%
“…42 Similar mechanisms of context dependent activity and nonadditive interactions have been observed for distinct enhancers in Arabidopsis that are acted upon by Polycomb group proteins, 43 and for the Caenorhabditis elegans endoderm regulator elt-2. 44 Overall, our experiments with the wg locus provide an additional example of nonadditive interactions between pair-rule responsive enhancers and further suggest that the nonadditive integration of inputs from different enhancers is a widespread aspect of regulating transcription in animal systems.…”
Section: Non-additive Interactions In Other Contextsmentioning
confidence: 60%